Comparison of outcomes in buried versus exposed Kirschner wire for treatment of paediatric supracondylar humerus fracture - Kafle, Gokul; Pokhrel, Anuja; Kumar Gupta, Mithilesh; Panthee, Rajan; Nepal, Santosh; Kumar Sah, Raj; Gautam, Ujwal (Birat Journal of Health Sciences, 2024)
Introduction: The treatment options for paediatric supracondylar distal humerus fractures include close reduction and above elbow slab application, close reduction and percutaneous K-wire fixation, and open reduction and internal fixation using K-wire. For displaced supracondylar fracture closed reduction and percutaneous K-wire fixation, under C-arm guidance, is the current gold standard treatment option. Leaving the K-wire exposed or buried under the skin is decided as per the discretion and convenience of the operating surgeon. Objectives: The objective of this study is to evaluate and compare the outcomes of buried and exposed K-wire for treatment of paediatric supracondylar humerus fractures. Methodology: This study is a prospective, comparative, observational study conducted among the paediatric patients visiting Birat medical college teaching hospital OPD/ emergency department with supracondylar humerus fracture. The sample size was calculated to be 90 (45 in each group) on the basis of convenience sampling and samples were collected using systematic random sampling technique. After data collection, all reports are entered in a predetermined Performa and analysed using SPSS version 21. Results: The overall complications rate was 20%. In the exposed K-wire group, 6 patients (13.33%) had surgical site infection at 4 weeks. Among them, 5 patients (11.11%) had superficial infection and 1 patient (2.22%) had deep infection. In the buried K wire group, only 2 patients (4.44%) had skin perforation and superficial infection. None of the patients had deep infection. There were 2 patients (4.4%) with hyper granulation tissue formation in exposed K wire group which were associated with superficial infection. There were 8 patients (17.8%) with skin irritation/ K wire prominence but without K wire perforation in the buried K wire group which was statistically significant (p value 0.006). Conclusion: There is no significant difference between the exposed K wire group and buried K wire group.